Clinical Management Of Generalized Anxiety Disorder (Chittodvega) Through Shirodhara With Mamsyadi Kwatha: A Comprehensive Case Report - Ayushi Chandil; Shraddha Sharma; Pooja Maida; Rajesh Meshram (International Journal For Multidisciplinary Research, 2026)
Background: Generalized Anxiety Disorder (GAD), structurally mapped to Chittodvega in Ayurvedic nosology, stems from a combined aggravation of Vata-Pitta Doshas alongside an elevation of Rajas and Tamas in the Manovaha Srotas. Standard psychopharmacological agents are often associated with dependency, sedation, and adverse cognitive effects.Case Presentation: A 34-year-old adult with a 7-month history of GAD, meeting DSM-5 diagnostic criteria, was managed with Shirodhara using warm Mamsyadi Kwatha (38–40°C) — a neuro-restorative decoction of Nardostachys jatamansi, Withania somnifera, and Hyoscyamus niger — administered daily for 30-minute sessions over 21 consecutive days.Outcome Measures: Symptom severity and sleep quality were assessed at Baseline (Day 0), Mid-Treatment (Day 10), and End of Treatment (Day 21) using the Hamilton Anxiety Rating Scale (HAM-A) and the Pittsburgh Sleep Quality Index (PSQI).Results: Total HAM-A score decreased from 28 at baseline to 10 at Day 21 (64% reduction), with psychic and somatic anxiety subscale scores improving by 68% and 59% respectively. The global PSQI score dropped from 14 to 5 (62% reduction), with sleep latency reduced from 52 to 18 minutes. No adverse events were observed.Conclusion: Shirodhara with Mamsyadi Kwatha provided a safe, multi-targeted intervention that dampened central nervous hyperarousal, restored autonomic equilibrium, and alleviated both somatic and psychic components of Chittodvega, suggesting potential as a non-pharmacological adjunct in GAD management.